Public Expenditure, Demography and Growth: Theory and Evidence from India - Pranab Kumar Das; Saibal Kar (Institute for the Study of Labor (IZA), 2016)
Many countries in the developed world are ageing in terms of their distribution of population. Conversely, a number of countries in the south have younger population. India for example, has 60% of its population in the age group of 15-59, with the mean age close to 27 years as of present times. The lower share of population in the higher and lower age brackets make the dependency ratio lower than that of the ageing countries. The economic growth such a large share of working age population can usher in lies at the core of the demographic dividends. However, low human capital, poor health and inadequate physical infrastructure seems to create significant hurdles in the potential growth path such countries can achieve. We investigate through an endogenous growth model applied to the Indian macroeconomic data, as to whether public expenditures in education, health and physical infrastructure are conducive to rapid economic growth commensurate with the projected demographic dividends for India. We deploy a Structural Vector Autoregressive Model on data for shares of public expenditure on education and health as the main pillars of growth of human capital in the country, on the per capita GDP growth rate, the working age population, etc. Importantly, we find that a rise in expenditure on health imparts a positive impact on the working age population through greater participation. However, higher allocations for education and training draws workers away from the labor market in a country with large share of unskilled workers and employment opportunities in the large informal sector.
Keywords: E24; E6; J2; N3; 330; human capital; health; endogenous growth; demographic dividend; public expenditure